Analysis of a phase-variable restriction modification system of the human gut symbiont Bacteroides fragilis. Issue 19 (12th October 2020) - Ben-Assa, Nadav; Coyne, Michael J; Fomenkov, Alexey; Livny, Jonathan; Robins, William P; Muniesa, Maite; Carey, Vincent; Carasso, Shaqed; Gefen, Tal; Jofre, Juan; Roberts, Richard J; Comstock, Laurie E; et al.
Abstract: The genomes of gut Bacteroidales contain numerous invertible regions, many of which contain promoters that dictate phase-variable synthesis of surface molecules such as polysaccharides, fimbriae, and outer surface proteins. Here, we characterize a different type of phase-variable system of Bacteroides fragilis, a Type I restriction modification system (R-M). We show that reversible DNA inversions within this R-M locus leads to the generation of eight specificity proteins with distinct recognition sites. In vitro grown bacteria have a different proportion of specificity gene combinations at the expression locus than bacteria isolated from the mammalian gut. By creating mutants, each able to produce only one specificity protein from this region, we identified the R-M recognition sites of four of these S-proteins using SMRT sequencing. Transcriptome analysis revealed that the locked specificity mutants, whether grown in vitro or isolated from the mammalian gut, have distinct transcriptional profiles, likely creating different phenotypes, one of which was confirmed. Genomic analyses of diverse strains of Bacteroidetes from both host-associated and environmental sources reveal the ubiquity of phase-variable R-M systems in this phylum.